2022
DOI: 10.1101/2022.07.07.22277349
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Wastewater-Based Epidemiology for SARS-CoV-2 Biomarkers: Evaluation of Normalization Methods in Small and Large Communities in Southern Germany

Abstract: In the context of the COVID-19 pandemic, wastewater-based epidemiology (WBE) emerged as a useful tool to account for the prevalence of SARS-CoV-2 infections on a population scale. In this study we analyzed wastewater samples from three large (> 300,000 people served) and four small (< 25,000 people served) communities throughout southern Germany from August to December 2021, capturing the fourth infection wave in Germany dominated by the Delta variant (B.1.617.2). As dilution can skew the SARS-CoV-2 biom… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Other than PMMoV, Hsu et al (2022) found that Paraxanthine was a more reliable population biomarker than PMMoV. Mitranescu et al (2022) reported that the best normalization performance was achieved with a mixed fecal indicator calculated from both CrAssphage virus and PMMoV. It is crucial to note that these divergent conclusions were primarily attributed to the choice of matrix (solids versus liquid) (D'Aoust et al, 2021;Wolfe et al, 2021) and variances in analytical methods (Scott et al, 2021;Zhan et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Other than PMMoV, Hsu et al (2022) found that Paraxanthine was a more reliable population biomarker than PMMoV. Mitranescu et al (2022) reported that the best normalization performance was achieved with a mixed fecal indicator calculated from both CrAssphage virus and PMMoV. It is crucial to note that these divergent conclusions were primarily attributed to the choice of matrix (solids versus liquid) (D'Aoust et al, 2021;Wolfe et al, 2021) and variances in analytical methods (Scott et al, 2021;Zhan et al, 2022).…”
Section: Discussionmentioning
confidence: 99%